Partisan Representation in Congress and the Geographic Distribution of Federal Funds - Albouy, David (The Review of Economics and Statistics, 2013)
In a two-party legislature, districts represented by the majority may receive greater funds if majority-party legislators have greater proposal power or disproportionately form coalitions with each other. Funding types received by districts may depend on their legislators' party identity when party preferences differ. Estimates from the United States, using fixed-effect and regression-discontinuity designs, indicate that states represented by members of Congress in the majority receive greater federal grants, especially in transportation, and defense spending. States represented by Republicans receive more for defense and transportation than those represented by Democrats; the latter receive more spending for education and urban development.